Penerapaan Strategi Make a Match untuk Meningkatkan Hasil Belajar PLH di Kelas II Materi Lingkungan Abiotik - Aufa, Ismi Nabila (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
This research was based on a preliminary study at SDN 221 Babakan Sentral where information was obtained that there was a lack of interest in learning from class II students in learning PLH on Abiotic Environment material. There are still many teachers who use conventional learning in delivering material, such as the lecture method which is still fully implemented, resulting in low student understanding and learning motivation. This research aims to improve student learning outcomes in PLH lessons. The design in this research is classroom action research (PTK) which consists of II cycles, and each cycle includes 4 stages, namely: planning, action, observation and reflection. Data will be collected through observation sheets and test questions. Using a cooperative learning model. The research results show that learning in PLH subjects with Abiotic Environment material through the application of the Make A Match strategy can experience an increase, namely in cycle I the percentage of student learning outcomes is only in the good category (68.14%), while in cycle II the percentage value of results Student learning increased to (85.92%) in the very good category. In conclusion, implementing the make a match strategy can improve student learning outcomes and is used effectively.